1996
DOI: 10.1007/s002530050796
|View full text |Cite
|
Sign up to set email alerts
|

Efficient selection of hygromycin-B-resistant Yarrowia lipolytica transformants

Abstract: The yeast Yarrowia lipolytica was shown to be sensitive to the aminoglycoside antibiotic hygromycin B. Spontaneous resistants appeared at a frequency of (2-5) x 10(-7) in media containing 100 mg/l drug. In order to develop a new selective marker for the transformation of this yeast, we constructed new plasmids expressing the Escherichia coli hygromycin-resistance gene (hph) under the control of the promoter and terminator sequences of the strongly expressed XPR2 gene of Y. lipolytica. Direct selection of hygro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…These results suggested that the lack of HYG gene expression in C. tropicalis was due to translation of the CTG codons as serines rather than leucines. Expression of the HYG gene failed in C. albicans (Leuker et al 1992), while it succeeded in S. cerevisiae (Gritz and Davies 1983) and Yarrowia lipolytica (Otero and Gaillardin 1996). It has been reported that the CTG codon, a universal leucine codon, is read as serine among several Candida species.…”
Section: Sensitivity Toward Hygromycin B Of C Tropicalismentioning
confidence: 96%
See 1 more Smart Citation
“…These results suggested that the lack of HYG gene expression in C. tropicalis was due to translation of the CTG codons as serines rather than leucines. Expression of the HYG gene failed in C. albicans (Leuker et al 1992), while it succeeded in S. cerevisiae (Gritz and Davies 1983) and Yarrowia lipolytica (Otero and Gaillardin 1996). It has been reported that the CTG codon, a universal leucine codon, is read as serine among several Candida species.…”
Section: Sensitivity Toward Hygromycin B Of C Tropicalismentioning
confidence: 96%
“…Resistance to G418 or hygromycin B is commonly used as a selectable marker in the selection of yeast transformants (Jimenez and Davies 1980;Gritz and Davies 1983;Otero and Gaillardin 1996). Unfortunately, C. tropicalis is highly resistant to G418.…”
mentioning
confidence: 99%
“…36,37) One can obtain positive transformants at high frequency by targeted integration, since there is low homology between the drug-resistance marker and the yeast genome. Moreover, those markers make it possible to transform wild-type strains that have not been subjected to heavy mutagenesis, and they provide a great advantage for use in the case of a high-ploidy yeast like C. utilis.…”
Section: Discussionmentioning
confidence: 99%
“…We have sequenced, assembled, and annotated the initial non-homologous end-joining mutant strain used for construction of all the strains described herein allowing for accurate design of genetic constructs. Although some of the resources we have developed have been previously described in other genetic backgrounds in Y. lipolytica [31], including auxotrophs [7], utilization of hph [114] and gfp [115], and replicating and integrating plasmids, they have guided the design of these strains and plasmids. Having all these tools, along with the fluorescent organelle atlas in an isogenic non-homologous end-joining mutant will remove data differences caused by genetic background, and expedite functional genetics in Y. lipolytica .…”
Section: Discussionmentioning
confidence: 99%